2012
DOI: 10.1371/journal.pone.0051869
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Tregs, Suppression of Th1 and Th17 Cells, and Amelioration of Experimental Allergic Encephalomyelitis by a Physically-Modified Saline

Abstract: In multiple sclerosis (MS) and other autoimmune diseases, the autoreactive T cells overcome the resistance provided by the regulatory T cells (Tregs) due to a decrease in the number of Foxp3-expressing Tregs. Therefore, upregulation and/or maintenance of Tregs during an autoimmune insult may have therapeutic efficacy in autoimmune diseases. Although several immunomodulatory drugs and molecules are available, most present significant side effects over long-term use. Here we have undertaken an innovative approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 41 publications
3
75
0
1
Order By: Relevance
“…Splenocytes were isolated from the spleens of treatmentnaïve CIA mice [18]. Spleens were aseptically removed from eight mice in each group and washed with cold PBS and the tissues were minced.…”
Section: Preparation Of Spleen Cell Suspensions From Cia Micementioning
confidence: 99%
See 1 more Smart Citation
“…Splenocytes were isolated from the spleens of treatmentnaïve CIA mice [18]. Spleens were aseptically removed from eight mice in each group and washed with cold PBS and the tissues were minced.…”
Section: Preparation Of Spleen Cell Suspensions From Cia Micementioning
confidence: 99%
“…Two-color flow cytometry was performed as described previously [18]. In brief, 1 9 10 6 splenocytes suspended in flow staining buffer were incubated at 4°C with FITClabeled anti-CD4 (eBioscience) for 30 min, washed and resuspended in fixation solution.…”
Section: Th17 Analysismentioning
confidence: 99%
“…Instead, both fluids are generated using a process involving TCP flow, which produces strong, controlled turbulence and cavitation events in the fluid. Research on RNS60 suggests that its bioactivity is based on the presence of nanobubblebased physical structures stabilized by an electrical doublelayer at the liquid/gas interface [8][9][10]. The exact nature of these nanostructures is under investigation and the descriptive term "charge-stabilized nanostructures" has been used to refer to these entities.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The group that consumed the EMW displayed lower blood levels of creatine kinase and high sensitivity CRP at 48 h and 96 h after exercise [18], thus indicating that less cell damage and inflammation occurred as a result of the exercise protocol. The bioactivity of RNS60 has been linked to effects on intracellular signaling pathways that influence cell stability and function [8][9][10]. Using a mouse model of Parkinson's disease, Khasnavis et al [8] showed that RNS60 improved locomotor function and reduced inflammation and neuronal degeneration in animals challenged with methyl-phenyltetrahydropyridine intoxication compared to a controlled saline.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation